Implementation of the Technology Acceptance Model (TAM) in analyzing the intention to use QRIS among students of Hidayatul Mubtadi'ien Islamic Boarding School Kotagede Yogyakarta - Muhammad Atho Burhanudin; Regas Panji Pratomo (Journal of Management Small and Medium Enterprises (SMEs), 2026)
The widespread adoption of digital payment systems has accelerated financial inclusion in Indonesia, with the Indonesian Standard Quick Response Code (QRIS) emerging as a key innovation in cashless transactions. However, understanding the factors that influence users’ intention to adopt QRIS remains essential, particularly within Islamic educational institutions. This study examines the effects of convenience, perceived usefulness, security, and trust on students’ intention to use QRIS at the Kotagede Hidayatul Mubtadi'ien Islamic Boarding School in Yogyakarta. A quantitative research design was employed using purposive sampling to collect data from 74 respondents. The proposed relationships were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The findings reveal that convenience and perceived usefulness have positive but statistically insignificant effects on students’ intention to use QRIS. In contrast, security and trust significantly and positively influence adoption intentions, highlighting the importance of users’ confidence in the reliability and safety of digital payment systems. The model explains 87.9% of the variance in QRIS usage intention, indicating substantial explanatory power. These results suggest that security and trust are the primary determinants of QRIS adoption among students in Islamic boarding school environments. The study contributes to the digital payment and financial technology literature by demonstrating that psychological and security-related considerations may outweigh functional benefits in shaping adoption intentions within specific cultural and institutional contexts. The findings provide practical implications for policymakers and payment service providers seeking to increase QRIS adoption through strategies that enhance system security, build user trust, and promote digital financial literacy among young consumers. Keywords: Convenience; Perceived Benefits; Security; Trust; Interest In Using QRIS